No evidence that established type 2 diabetes susceptibility variants in the PPARG and KCNJ11 genes have pleiotropic effects on early growth. - Bennett, A; Sovio, U; Ruokonen, A; Martikainen, H; Pouta, A; Hartikainen, A; Franks, S; Elliott, P; Järvelin, MR; McCarthy, M (2008)
AIMS/HYPOTHESIS: The P12A variant in the PPARG gene and the E23K polymorphism in KCNJ11 are both known to influence individual predisposition to type 2 diabetes. If the effect of these variants on insulin secretion and action were to extend to an influence on early growth (which is largely mediated by insulin), it would offer an explanation for observed associations between low birthweight and subsequent diabetes. Since previous studies of the effects of these variants on early growth have been limited and conflicting, we examined these associations in a large, well-characterised birth cohort. METHODS: The P12A and E23K variants were genotyped in (respectively) 5,652 and 5,632 individuals from the Northern Finland Birth Cohort of 1966 and we sought associations with early growth phenotypes. RESULTS: Neither variant was associated with birthweight (P12A, p = 0.42; E23K, p = 0.44, additive models) or other measures of early growth. Although a previous report had suggested that the P12A effect on adult insulin sensitivity was restricted to small babies, we were unable to reproduce this finding (p = 0.40), nor did we confirm a previous report of an association with gestational age (p = 0.23). CONCLUSIONS/INTERPRETATION: Despite a larger sample size than previous studies, we were unable to detect any effect of these variants on early growth. These findings do not support the notion that there are shared genetic determinants of low birthweight and adult diabetes.